Different roles of soluble CD40 ligand in central nervous system damage. (3rd May 2020) - Du, Li; Chang, Haoxiao; Wei, Yuzhen; Zhang, Xinghu; Yin, Linlin
ABSTRACT: Backgroud and purpose : Soluble CD40 ligand (sCD40L) plays an important role in inflammation and autoimmune disorders. There is still a controversy regarding sCD40L in neuromyelitis optica spectrum disorders (NMOSD) and multiple sclerosis (MS). Herein the aims of this study were to evaluate the levels of sCD40L in patients with NMOSD, MS, and other noninflammatory neurological diseases; to investigate its potential relationship with laboratory parameters, glial fibrillary acidic protein (GFAP), thrombopoietin (TPO) and IL-6; and to address whether serum sCD40L levels in acute attacks of NMOSD patients were decreased after treatment with immunoglobulins, plasma exchange, or methylprednisolone.Materials and methods : We enrolled 13 patients with NMOSD, 9 patients with MS, and 9 patients with other noninflammatory neurological diseases. The levels of sCD40L, IL-6 were measured by cytokine multiplex assay. GFAP levels were measured by ELISA.Results:  Both serum and cerebrospinal fluid (CSF) sCD40L levels were increased in NMOSD and MS. No differences were found in serum and CSF sCD40L levels between NMOSD and MS. The CSF sCD40L levels were positively correlated with the CSF cell counts in NMOSD, whereas serum sCD40L levels were positively correlated with the albumin index in MS. Furthermore, the levels of CSF sCD40L were positively correlated with CSF GFAP levels in NMOSD. Serum sCD40L levels were correlated with serum TPO levels in MS. No correlation was found between levels of sCD40L and IL-6 in NMOSD and MS. No statistically meaningful difference between NMOSD patients with or without immunotherapy. Conclusions : Our study suggests that sCD40L can contribute to the destruction of the blood-brain barrier in MS, whereas it may contribute to CNS inﬂammation in NMOSD. The serum sCD40L concentrations were not changed after treatment with immunoglobulins, plasma exchange, or methylprednisolone in acute attacks of NMOSD.